Detection of plasmid-mediated quinolone resistance determinants and qnrS expression in Enterobacteriaceae clinical isolates - Xiaobing Jiang; Jun Li; Yunshan Zhang; He Yan; Yuxiao Wang; Lei Shi; Lijun Zhou (Journal of Infection in Developing Countries)
Introduction: Rapid dissemination of plasmid-mediated quinolone resistance (PMQR) has been reported in clinical isolates. Methodology: A total of 149 clinical isolates of Enterobacteriaceae were collected in Beijing and screened for PMQR genes usingpolymerase chain reaction (PCR). Real-time quantitative PCR was used to study the expression of qnrS. Results: The rates of qnr and aac(6’)-Ib-cr genes were 7.4% and 8.1%, respectively. The higher basal expression of qnrS was observed in transconjugant strains, which had higher minimum inhibitory concentrations (MICs) of quinolones. Furthermore, qnrS expression levels increased in all three isolates when a quinolone was present. Conclusions: Our data suggest that the level of qnrS expression was associated with quinolone resistance.